OP0345 Denosumab compared with risedronate in glucocorticoid-treated subjects: results from the final 24-month analysis of a randomised, double-blind, double-dummy study. (12th June 2018) - Saag, K.G.; Pannacciulli, N.; Geusens, P.; Adachi, J.D.; Messina, O.D.; Morales-Torres, J.; Emkey, R.; Butler, P.W.; Yin, X.; Lems, W.F.
Abstract : Background: Denosumab 60 mg subcutaneously Q6M increased spine and hip BMD significantly more than risedronate 5 mg orally QD at 12 months in glucocorticoid-treated subjects (as previously reported¹). Objectives: This analysis compared the BMD effects of denosumab vs risedronate and further characterised denosumab safety in this population at 24 months. Methods: This phase 3, randomised, double-blind, double-dummy study enrolled adults≥18 years receiving ≥7.5 mg daily prednisone (or equivalent) for <3 months (glucocorticoid-initiating subpopulation) or ≥3 months (glucocorticoid-continuing subpopulation). All subjects<50 years had history of osteoporotic fracture. Glucocorticoid-continuing subjects≥50 years had lumbar spine (LS), total hip (TH), or femoral neck BMD T-scores ≤–2.0, or ≤–1.0 and history of fracture. Subjects were randomised 1:1 to denosumab 60 mg subcutaneously Q6M or risedronate 5 mg orally QD for 24 months. This analysis assessed denosumab superiority over risedronate for percentage change from baseline in LS and TH BMD at 24 months. Results: Of 795 randomised subjects, 590 (74.2%) completed the 24 month study (glucocorticoid-initiating: 109/145 denosumab, 117/145 risedronate; glucocorticoid-continuing: 186/253 denosumab, 178/252 risedronate). Denosumab was superior to risedronate for increases from baseline in LS and TH BMD at all timepoints assessed through 24 months in each subpopulation (figure 1). Adverse events, serious adverse events (including infection), and fractures were similar between groups. Conclusions: In conclusion, denosumab was superior to risedronate for increases in spine and hip BMD through 24 months. The overall safety profile was similar between groups. Denosumab may offer a valuable osteoporosis treatment option for patients receiving glucocorticoids. Reference: [1] Saag K, Wagman RB, Geusens P, et al. Effect of denosumab compared with risedronate in glucocorticoid-treated individuals: Results from the 12-month primary analysis of a randomized, double-blind, active-controlled study. Ann Rheum Dis2017:76(Suppl 2):54. Acknowledgements: This study was funded by Amgen Inc. Jonathan Latham (PharmaScribe, LLC) and Lisa Humphries (Amgen Inc.) provided medical writing support. Disclosure of Interest: K. Saag Grant/research support from: Amgen, Merck, Consultant for: Amgen, Lilly, Merck, Radius, N. Pannacciulli Shareholder of: Amgen, Employee of: Amgen, P. Geusens Grant/research support from: Abbott, Amgen, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Pfizer, Roche, UCB, Will-Pharma, Consultant for: Amgen, Lilly, J. Adachi Grant/research support from: Amgen, Consultant for: Amgen, Employee of: McMaster University, Speakers bureau: Amgen, O. Messina: None declared, J. Morales-Torres Consultant for: Amgen, Speakers bureau: Amgen, R. Emkey Speakers bureau: Amgen, P. Butler Shareholder of: Amgen, Employee of: Amgen, X. Yin Shareholder of: Amgen, Employee of: Amgen, W. Lems Consultant for: Amgen, Eli Lilly, Merck, Speakers bureau: Amgen, Eli Lilly, Merck